Case Report on Hemangioma - Porwal, Surya; Bhatia, Gouri; Attresh, Gyanander; Batra, Jitender; Garg, Balram; *, Kirtika (IJRDO - JOURNAL OF BIOLOGICAL SCIENCE, 2015)
Vascular anomalies comprise a widely heterogeneous group of tumours andmalformations. Haemangioma is the most common benign tumour of vascularorigin of head and neck region most commonly found on lips, tongue, buccalmucosa and palate. Despite of its benign origin and behaviour, it is always ofclinical importance to the dental profession and requires appropriate management.This case of palatal haemangioma mimicked itself as multiple palatal abscesses onvisual examination that lead to the confusion. The objective of this case report is tocreate awareness and familiarity to such an unusual presentation so that the lesioncan be diagnosed and managed appropriately.   This case report brings out a new dimension to a periodontist, the way ahaemangioma can present and the importance of appropriate diagnosis andmanagement, as haemangioma can lead to a life threatening bleeding.